1997
DOI: 10.1042/bj3250779
|View full text |Cite
|
Sign up to set email alerts
|

Nramp1 locus encodes a 65 kDa interferon-γ-inducible protein in murine macrophages

Abstract: The murine Nramp1 (natural-resistance-associated macrophage protein) locus, formerly known as Ity/Lsh/Bcg, was isolated previously on the basis of chromosomal location, and as conferring natural resistance to infection against intracellular macrophage pathogens. The gene encodes a transporter molecule of unknown function. We have prepared polyclonal antisera against the C-terminal 35 amino acids of murine Nramp1. This serum is reactive towards a 65 kDa protein, expressed in murine macrophage cells from resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 33 publications
(42 reference statements)
4
50
0
1
Order By: Relevance
“…Nramp2 transports a range of metal ions including Fe, Mn, Zn, Cd, Cu, and Co with about the same efficiency [13]. In addition, recent reports show that Nramp1 is associated with phagocytic vesicles of the late endocytic pathway [16,17]. Taken together, these results suggest that Nramp1 functions to transport metal ions in or out of the macrophage phagosomes after infection with an intracellular pathogen.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Nramp2 transports a range of metal ions including Fe, Mn, Zn, Cd, Cu, and Co with about the same efficiency [13]. In addition, recent reports show that Nramp1 is associated with phagocytic vesicles of the late endocytic pathway [16,17]. Taken together, these results suggest that Nramp1 functions to transport metal ions in or out of the macrophage phagosomes after infection with an intracellular pathogen.…”
Section: Introductionmentioning
confidence: 69%
“…Gruenheid et al [16] reported that in resting macrophages Nramp1 is localized to late endocytic vesicles containing lysosomal-associated membrane protein 1 (Lamp1) that on phagocytosis fuse with the phagosomes. Atkinson et al [17] showed that Nramp1 is associated with endosomal vesicles formed in macrophages by phagocytosis of magnetic IgG-coated beads. A more detailed study by this group using M. avium infection produced similar results [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were harvested at intervals for Nramp1 expression determination and for cell growth quantitation. N11 microglial cells that express mature 90-to 100-kDa Nramp1 protein were used for analysis of Nramp1 regulation following serum removal and replacement and were maintained as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
“…60 Increased iron concentrations increase M. avium growth within macrophages, and when excess iron is present the greater ability of Nramp1 G169/G169 mice compared to Nramp1 D169/D169 mice to limit M. avium replication is overcome. 61 This suggests that Nramp1 may be an iron transporter which is saturated at high iron concentration.…”
mentioning
confidence: 99%